Advancing coupling coordination simulation in the social-human-ecological system of the Three Gorges Reservoir Area: A multi-scenario system dynamics approach - Cheng, Guo; Li, Guiyuan; Pu, Xiangjun; Chen, Chi; He, Yu (Ecological indicators, 2024)
•The multi-scenario simulation of the coupling coordination degree between the social-human-ecological system.•The research incorporate the human system innovatively into the socio-ecological system.•Counties and districts have varied CCD development pathways.•Simply increasing the policy intensity of a single subsystem is inadequate.•The results provide guidance for the formation of high-quality and sustainable socio-economic policies. Due to the lack of scientific and systematic thinking in the early stages of high-quality urbanisation, the interaction and stress between the social-human-ecological (SHE)11SHE social-human-ecological. system intensified, resulting in a series of problems related to the low level of ecological environment and the imbalanced socio-economic development. It is crucial to enhance the safety, health, and well-being of city dwellers, as well as to promote the sustainable development of the region. Based on complex systems science, using the Three Gorges Reservoir Area (TGRA)22TGRA Three Gorges Reservoir Area. as an instance, this study develops a multidimensional coupling conceptual model of the SHE system, employs the system dynamics (SD)33SD system dynamics. method to clarify the SHE system’s causal feedback mechanism, and simulates the coupling coordination degree (CCD)44CCD coupling coordination degree. from 2010 to 2030. Simultaneously, eight scenarios are created to improve the system’s CCD by modifying factors. According to historical and sensitivity test findings, the SD model used in this work can effectively represent the SHE system’s dynamic coupling and interaction connection. Furthermore, under the comprehensive development scenario that takes into account the protection of the ecological environment, human intelligent regulation, and socio-economic development, the TGRA has the biggest growth in CCD. As a result, raising the policy intensity of a single subsystem is insufficient. Balancing policy implementation for each subsystem is advantageous to improving the coupling coordination of the SHE system in the TGRA. The study is of significant importance for achieving high-quality socio-economic development and sustainable ecological management in the TGRA region.